Population genetics of Liriomyza trifolii (Diptera: Agromyzidae) and comparison with four Liriomyza species in China based on COI, EF-1a and microsatellites loci - Chen, Jing-Yun (Sci Rep, 2019)
Liriomyza is a large genus that includes polyphagous and invasive species (L. trifolii, L. sativae, and L. huidobrensis), and oligophagous species such as L. Chinensis in China. Effective control of these invasive and oligophagous species is not easy due to the fast invasion rate, interspecific competition, and pesticide resistance. In this study, we investigated population genetics of five Liriomyza species L. trifolii, L. sativae, L. huidobrensis, L. bryoniae, and L. chinensis based on COI and EF-1a genes, and microsatellite DNA. These five Liriomyza species revealed highly conservative characteristics in the COI gene among populations collected from different geographical regions and host plants. By contrast, the mutation rate of the EF-1a gene was higher than COI, and phylogenetic tree based on EF-1a showed that haplotypes of L. trifolii and L. sativae were not distinguished well. Genetic differentiation in microsatellite loci was obvious among the five species. Our results also indicated that geographic isolation had a greater impact on genetic differentiation in L. trifolii than the host plant. Populations of L. trifolii in China showed a high to moderate level of genetic differentiation and they had divided into two groups representing the coastal areas of southern China and northern regions. The genetic diversity of the southern group was higher than the northern group. We speculated that the invasion of L. trifolii likely occurred in southern regions of China and then spread northward. Bottleneck analyses revealed that the L. trifolii population in China was in a steady growth period.